NILAI KELUARGA DALAM FILM COCO PRODUKSI WALT DISNEY PICTURES - Toloh, Gloria Victoria; Wantasen, Isnawaty L.; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACKThe research is entitled â€œFamily Value in Film Coco by Walt Disney Pictureâ€. Â It is written to fulfill the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities Sam Ratulangi University. Coco is an animated movie that tells the story of Miguel, a boy from the Rivera family who is very fond of music and he wants to be a musician, but the Rivera family is phobia with music. This research is about family value. Â The purpose of this research are identify classify and analyze the theme in the Film Coco through the characters, plot and setting. The method used in this research is primary method. The writer uses the theory of family value from Lammana and Riedman (1990) to analyze and describe the family values in the movie. The result of this research is that the value in our family is important, through the values in the family we can know and understand the meaning of a family. There are three types of family values: togetherness, stability, and loyalty, through conflict and the plot. Keywords: animation film, family value, culture